Implementasi Psikoedukasi Empat Kata Ajaib Untuk Meningkatkan Etika Sosial Siswa Kelas 1 Sekolah Dasar Pertiwi Makassar - Sufartianinsih Jafar, Eka; Zulfa Afiva, Andi; Ruhana; Yahdini Firsyah Nadhirah, Andi; Mutiara, Anggun (CV. Multi Kreasi Media, 2024)
Character education in school-age children, including elementary school students especially grade 1, is the initial foundation for their future growth and development. School-age children are defined as those aged between 6 and 12 years old. In this age range, school is an important part of children's development as they begin to take responsibility for their actions in interacting with their peers and adults. Character education at this school age can help shape children's behavior, ethics, and attitudes that will affect their future. This study aims to apply the four magic words psychoeducation and observe its impact on the social ethics of grade 1 students. Through a descriptive qualitative approach, this study describes the process and outcomes of the psychoeducation activities conducted in two grade 1 classes at SD Pertiwi Makassar. The implementation method of this program involved observation, interaction, and student responses during the activities. The preparation stage involved creating materials on the four magic words: “please”, “thank you”, “sorry”, and “excuse me”, as well as the use of videos to sing the four magic words song. The implementation stage included distribution of materials, literacy or reading of materials, reflection through discussion, and a sing-along activity. The results showed that this psychoeducational approach was successful in improving the understanding and use of the four magic words in daily social interactions. Students not only understood the concepts, but also showed consistent application during and after the activity. The conclusion of this study is that the application of four magic words psychoeducation is effective in improving the social ethics of grade 1 students. The descriptive qualitative approach allowed the researcher to get an in-depth picture of the study.